A Comparison of the efficacy of cetirizine and terfenadine in chronic idiopathic urticaria - Chatterjee G; Banerjee PK (Wolters Kluwer Medknow Publications, 1996)
ABSTRACT: In a 10 d, double blind, randomized, parallel study, the efficacy of cetirizine and terfenadine was compared in 30 patients with chronic idiopathic urticaria. Subjects were randomly divided into two patient groups of 15 each. The first group was given cetirizine (10 mg once daily) and the second terfenadine (120 mg once daily). Cetirizine proved to be more effective than terfenadine in controlling urticaria symptoms. In fact, the score of the investigators′ overall assessment was significantly lower in cetirizine-treated group than in terfenadine-treated group. Moreover, patients′ evaluation of symptoms assesed on a four point scale showed a better improvement in the cetirizine group. The number and severity of side-effects were similar in both the groups.